A novel Pd3O9@α-Al2O3 catalyst under a hydroxylated effect: high activity in the CO oxidation reaction. Issue 48 (26th August 2015) - Li, Qiaohong; Wei, Yongqin; Sa, Rongjian; Ma, Zuju; Wu, Kechen
Abstract : A new Pd3 O9 @α-Al2 O3 catalyst has been designed which shows superior catalytic activity for CO oxidation. Abstract : Considering the importance of palladium-based and doped metal-oxide catalysts in CO oxidation, we design a new Pd3 O9 @α-Al2 O3 catalyst and simulate its efficiency under a hydroxylated effect. The structure, electronic structure and oxidation activity of the hydroxylated Pd3 O9 @α-Al2 O3 (0001) surface are investigated by density functional theory. Under the O-rich growth conditions, Pd preferentially replaces Al. The lowest formation energy of the Pd-doped α-Al2 O3 (0001) surface is 0.21 eV under conditions wherein the coverage of the Pd-doped α-Al2 O3 is 0.75 on a pre-hydroxylated surface and the water coverage is 0.25, which leads to formation of a Pd3 O9 cluster embedded in the Al2 O3 (0001) surface. The reaction mechanisms of CO oxidization have been elucidated first by CO adsorption and migration, second by Ov formation with the first CO2 release, then by the first foreign O2 filling and CO co-adsorption, and finally by the second CO2 desorption and restoration of the hydroxylated Pd3 O9 @α-Al2 O3 (0001) surface. The rate-determining step is the formation of the first CO2 in the whole catalytic cycle. The results also indicate that the energy barrier for CO oxidization is obviously reduced compared to that of the undoped surface, which implies that the introduction of Pd can efficiently improve the oxidation reactivity of the α-Al2 O3 (0001) surface. Compared to the synthesized Ir1 /FeO x (1.41 eV) and Pt1 /FeO x (0.79 eV) catalysts, the reaction activation barrier of CO oxidation is lowered by 0.65 eV and 0.03 eV, respectively. Therefore, the Pd3 O9 @α-Al2 O3 catalyst shows superior catalytic activity in CO oxidation. The present results enrich the understanding of the catalytic oxidation of CO by palladium-based catalysts and provide a clue for fabricating palladium-based catalysts with low cost and high activity.